Control over coordination self-assembly of flexible, multidentate ligands by stepwise metal coordination of isopyrazole subunits. Issue 3 (4th January 2019) - Ashida, Yoshiko; Manabe, Yumehiro; Yoshioka, Shota; Yoneda, Tomoki; Inokuma, Yasuhide
Abstract : Structural convergence of the self-assembly of flexible oligoisopyrazoles was controlled by stepwise palladium coordination and discrete complexes with structural diversity were selectively generated in a predictable fashion. Abstract : Structurally flexible oligoisopyrazole molecules were self-assembled into discrete complexes with structural diversity upon palladium coordination. Structural convergence was controlled by a stoichiometry change to induce stepwise metal coordination of isopyrazole subunits. Three different types of complexes were selectively generated from a diisopyrazole ligand. Furthermore, tetraisopyrazole ligands were quantitatively assembled into a discrete complex in a predictable manner.